Equilibrium to equilibrium dynamics in a climate change economy - Song, Edward (Munich, 2016)
"Different from past economic research, I incorporate recent theories by climatologists that burning fossil fuels increases the equilibrium level of carbon dioxide, CO2, in the atmosphere into a macroeconomic growth model. In the model, both production and consumption produces $CO_2$ emissions. I also assume that Anthropogenic Global Warming, AGW, not only damages production, but also capital stock and utility. In addition, a boundary condition similar to the Simpson-Kombayashi-Ingersoll (SKI) Limit holds, that there exists a critical temperature which leads to runaway greenhouse warming. Under these assumptions with no alternative fuel sources, and unlimited fossil fuel supply, the economy eventually flat lines (dies). Abatement only delays the inevitable. Using discount factors of .95 and .99, modest abatement policy can increase world welfare but do not increase life expectancy. When the discount factor is zero, conclusions of which policy is best is sensitive to the time horizon policy makers use. If a 100 year time horizon is used, modest consumption abatement may be the best policy, which may actually decrease life expectancy. However, a theoretical infinite time horizon may imply near zero emissions as the growth of damages is reduced and the probability of survival increases. Unfortunately, because humans have finite lives, this creates an ethical dilemma. In order for society to be better off, the current living must sacrifice by accepting policies that lead them to experience near zero output, consumption and near zero lifetime utility and welfare."